Feasibility analysis of gesture recognition based human wearable electronic accessories - Taki, Khan Sakib Nur; Tonny, Jannatul Ferdous; Nahin, S.H.M (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.